Biphoton generation using multistate quantum key distribution technique - Abdullah M.S.; Jamaludin M.Z.; Witjaksono G.; Mokhtar M.H.H. (2023)
In this paper, we present a method to prepare pairs of photons (biphotons) for multistate quantum key distribution by investigating a pulsed laser diode driver system based on MOSFET current mirror and digital signal controller (DSC). The design is able to emit stream pairs of photons from three semiconductor laser diodes. The DSC is capable to switch between the three laser diodes at constant rate. The duty cycle is maintained at 1% in order to reduce its thermal effect and thus prolong the laser diodes life cycle. This laser driver system is capable to generate biphotons automatically with bit rate of about 5.5kbps for ? equal to 1. 2010 IEEE.